Nanomechanics and co-transcriptional folding of Spinach and Mango - Jaba Mitra (Nature Portfolio, 2019)
Light-up aptamers are widely used for fluorescence visualization of non-coding RNA in vivo. Here the authors employ single-molecule fluorescence-force spectroscopy to characterize the mechanical responses of the G-Quadruplex based light-up aptamers Spinach2, iMangoIII and MangoIV, which is of interest for the development of improved fluorogenic modules for imaging applications.